The implementation of European standards of higher education in the teaching of technical disciplines for future engineers-teachers - Kiporenko А. (Problems of Engineer-Pedagogical Education, 2018)
The article presents a critical analysis of the process to ensure the quality of education at the present stage of scientific and economic development of Ukraine. The main problems in ensuring the quality of higher education are tasked and solve them. We consider the European system of quality assurance, objectives and requirements for the quality of higher education, and European quality standards, which are the basis of its functioning. On the basis of analytical study systematically the basic requirements and the direction of the implementation of European standards in the educational space of the university as a separate division responsible for the training of future engineers-teachers, namely "Graduate Department". It is proposed to distribute the educational work done by "Graduate Department" in areas of implementation of European standards of higher education. On the basis of the suggested directions presented ways for improving educational activities with stakeholders position (student, teacher, employer, providing staff). Presents advantages in the implementation of educational activities units "Graduate Department" in the preparation of future engineers-teachers, in accordance with the directions of quality assurance in accordance with the European standards of higher education.